2015
DOI: 10.1051/epjconf/20159401041
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of unidirectional carbon fiber reinforced polyamide-6 thermoplastic composite under longitudinal compression loading at high strain rate

Abstract: Abstract. In the presented work, an experimental investigation has been performed to characterize the strain rate dependency of unidirectional carbon fiber reinforced polyamide-6 composite for longitudinal compression loading. An end-loaded compression specimen geometry, suitable for contactless optical strain measurement via digital image correlation and dynamic loading in a split-Hopkinson pressure bar, was developed. For the dynamic experiments at a constant strain rate of 100 s −1 a modified version of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…It can be concluded that the material is not strain rate dependent and the measurement of dynamic strain by DIC allows a more accurate comparison with respect to the measurement of the quasi-static strain by the video strain gauge system. PPSCFC mechanical behavior discussed does not coincide with the behavior observed on similar materials (thermoplastic matrixes reinforced with carbon fiber) [11,16,19,23,27,38]. This can be explained by the effect of carbon fiber on the resin (PPS) crystallization reported in open literature, where it has been found that transcrystallinity on the fiber-resin interphase affects the mechanical properties of the composite [32,38,[47][48][49].…”
Section: Mechanical Property Comparison For Ppscfcmentioning
confidence: 97%
See 3 more Smart Citations
“…It can be concluded that the material is not strain rate dependent and the measurement of dynamic strain by DIC allows a more accurate comparison with respect to the measurement of the quasi-static strain by the video strain gauge system. PPSCFC mechanical behavior discussed does not coincide with the behavior observed on similar materials (thermoplastic matrixes reinforced with carbon fiber) [11,16,19,23,27,38]. This can be explained by the effect of carbon fiber on the resin (PPS) crystallization reported in open literature, where it has been found that transcrystallinity on the fiber-resin interphase affects the mechanical properties of the composite [32,38,[47][48][49].…”
Section: Mechanical Property Comparison For Ppscfcmentioning
confidence: 97%
“…Data acquisition and conditioning system signals were post-processed using an in-house Python program, which computes the stress, strain, and strain rate on the specimen using the classical SHPB analysis based on the one-dimensional wave propagation theory, which implies elastic deformation in the bars during the tests, unidirectional elastic pulses propagate along the bars, uniform deformation process in the specimen, and no dispersion of waves throughout the bars and the specimen [11,24,26,28,29].…”
Section: Dynamic Testmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies were performed in recent years on the strain rate effect on the mechanical properties of thermoplastic composites [38][39][40][41][42][43]. Few works [44][45][46] were reported on the dynamic compressive response of polyamide composites. Strain-rate dependency is one of the material behaviors of fiber reinforced composites being focused on because many primary structural applications involve exposure to impact and crash loads.…”
Section: Introductionmentioning
confidence: 99%